Evaluation of bladder shape using transabdominal ultrasound: Feasibility of a novel approach for the detection of involuntary detrusor contractions. (August 2019) - Gray, Thomas; Phillips, Luned; Li, Weiguang; Buchanan, Charlotte; Campbell, Patrick; Farkas, Andrew; Abdi, Shahram; Radley, Stephen
Conventional assessment of overactive bladder syndrome uses invasive pressure-measuring catheters to detect bladder contractions (urodynamics). We hypothesised that bladder shape changes detected and measured using transabdominal ultrasound scan could provide a non-invasive and clinically useful alternative investigation of bladder contractions. This feasibility study evaluated a novel transabdominal ultrasound scan bladder shape test during conventional urodynamics and physiological bladder filling. The aim was to initially evaluate and refine a non-invasive approach for detecting and quantifying bladder shape changes associated with involuntary bladder contractions. To develop measurement techniques and characterise bladder shape changes during bladder filling, healthy female volunteers (n=20) and women with overactive bladder symptoms who had previously undergone urodynamics (n=30) completed symptom questionnaires and bladder diaries. The bladder shape test protocol included consumption of 1 l water before undergoing serial transabdominal ultrasound scan imaging of the bladder during physiological bladder filling and during episodes of urgency. In a further group of women with overactive bladder (n=22), serial transabdominal ultrasound scan images were captured during urodynamics so that shape changes occurring with bladder contractions could be characterised. In both healthy volunteers and women with overactive bladder, the transverse view of the bladder provided the most reliable plane to characterise and measure bladder shape changes. A sphericity index derived from the ratio between maximum inscribed and minimum circumscribed ellipses (πac 2(inner) /πac 2(outer) ) offered a reliable and reproducible measurement system. Of participants undergoing transabdominal ultrasound scan during urodynamics, there were significant measurable differences in sphericity index between patients with bladder contractions (n=12) and patients with acontractile bladders ( p < 0.001). Bladder shape changes detected during physiological filling and urodynamics have provided preliminary evidence to support further research into bladder shape test as a non-invasive diagnostic tool to identify involuntary bladder contractions in patients with overactive bladder syndrome.